87.6k views
1 vote
I really am struggling with this, could I have some help?

I really am struggling with this, could I have some help?-example-1

1 Answer

5 votes

f(x)-g(x)=x^2\text{ - 2x + 6}Step-by-step explanation:
\begin{gathered} \text{Given:} \\ f(x)=x^2\text{ + 1} \\ g(x)\text{ = }2x\text{ - 5} \end{gathered}

We are to find f(x) - g(x):

We will subtract the expressions of g(x) from f(x)


\begin{gathered} f(x)-g(x)=x^2\text{ + 1 - (2x - 5)} \\ \end{gathered}

Expanding the parenthesis using distributive property:


\begin{gathered} f(x)-g(x)=x^2\text{ + 1 - (2x) -(-5)} \\ mu\text{ltiplication of same signs gives positive sign} \\ m\text{ ultiplication of opposite signs give negative sign} \\ \\ f(x)-g(x)=x^2\text{ + 1 -2x + 5} \end{gathered}

collect like terms:


\begin{gathered} f(x)-g(x)=x^2\text{ -2x + 5 }+\text{ 1} \\ f(x)-g(x)=x^2\text{ - 2x + 6} \end{gathered}

User Bryan E
by
5.9k points